Earnings management in emerging markets: The COVID-19 and family ownership - Safia Abdo Ali Al-Begali; Lian Kee Phua (Cogent Economics & Finance, 2023)
This paper investigates the impact of COVID-19 and family ownership on earnings management (EM), both accruals (DA) and real (REM). This research also seeks to determine whether there is a substitutional or complementary relationship between DA and REM.The study's sample includes firms listed on the Jordanian market after excluding the banking and insurance sectors from 2017 to 2021. It used feasible generalised least squares estimation (FGLS) regressions to achieve the study's goals. The results reveal a negative and significant correlation between COVID-19 and discretionary accruals (DA), which indicates that COVID-19 restricts DA in Jordanian companies. However, the outcome shows a significant positive relationship between COVID-19 and REM, which indicates that COVID-19 encourages Jordanian companies to practice REM. According to the entrenchment theory, the majority shareholders in a family-owned business environment seek to expropriate the rights of the minority shareholders. Consistent with this theory, the result documents a significant positive correlation between family ownership and DA, indicating that high family ownership manages earnings through accruals. However, this study finds a significant negative relationship between family ownership and REM, indicating that a high concentration of family ownership restricts the practice of REM. This finding aligns with the alignment theory, which argues that the interests of minority and majority shareholders are compatible. These findings indicate a lack of accuracy and reliability in the financial reports in the Jordanian industrial and service enterprises due to the practicing DA by the family-owned companies as well as the outbreak of COVID-19 that led to a rise in the practice of REM. Finally, the findings document that Jordanian companies use REM and DA as complementary tools to maximise their impact on earnings. The findings of earlier research on EM who have used Jordanian-listed companies might not be beneficial in light of the current COVID-19 pandemic. Thus, the current study is one of the first empirical attempts to examine the impact of the COVID-19 pandemic and family ownership on the quality of financial reporting using both EM (DA and REM) in the context of the Jordanian market. The current study's findings are an important contribution to the literature on how family ownership affects the quality of financial reporting (QFR) and how COVID-19 affects the practice of EM. Therefore, the findings of this study can provide all stakeholders with information regarding the QFR in family-controlled companies and explore the accounting implications of the pandemic in order to assist all interested parties, particularly those in developing markets, in making more informed decisions.
Keywords: 330; AEM; COVID-19; earnings management; family ownership; Jordanian companies; REM